Studi Kinerja Solar Water Heater Dengan Aliran Zig-zag Beralur Balok - Ikhsan, M. Rizki; Soeparman, Sudjito; Sasongko, Mega Nur (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2017)
Solar energy can be used for water heating by using solar water heater application. Therefore, its still needs some modification due to its low efficiency. This modification can be done by replacing the conventional plate of solar collectors into a double plate with a zig-zag pattern. The results shown that along with the decreasing of water flow rates could significantly increase the useful energy (Qu). Initial temperature of water inlet could affect the generated maximum temperature. The highest mean efficiencies of double plate solar water heater with a zig-zag grooved beams pattern of 49.11% was gained in the flow rate of 700 mL / min.